Effect of freezing rate and frozen storage on the rheological properties and protein structure of non-fermented doughs. (March 2021) - Yang, Jingjie; Zhang, Bo; Zhang, Yingquan; Rasheed, Mohsin; Gu, Shuqin; Guo, Boli
Abstract: The objective of this study was to investigate the effects of the freezing rate and frozen storage duration on the rheological properties and protein structure of the non-fermented dough. The samples were frozen at −40 (0.149 °C/min), −30 (0.086 °C/min) and −20 °C (0.039 °C/min), and stored at −18 °C for 30 days. Freezing at −40 and −30 °C led to minimal changes in the rheological properties of the non-fermented dough. Additionally, −40 °C freezing resulted in higher maximum creep compliance ( J max ) and lower zero shear viscosity ( η 0 ). The content of glutenin macro-polymers (GMP) decreased gradually throughout the storage period, while that of free thiol groups (-SH) increased significantly, especially for samples frozen at −20 °C. Fourier transform infrared (FTIR) spectroscopy showed that slower freezing rate and prolonged storage led to a significant decrease in the proportion of α- helices, and a notable increase in that of β- sheets and random coils. The gluten network was severely deteriorated by a slower freezing rate but was relatively intact in the −40 and −30 °C frozen dough samples. Highlights: In this study, −40 °C (0.149 °C/min) freezing was optimum for non-fermented dough. At the optimal freezing conditions, the dough had better rheological properties. High freezing rate protects the structural stability of the non-fermented dough. More disrupted and weak structure were observed in the dough freezing at slow rate. A slow freezing rate with prolonged storage time obtained the most negative effects.